THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON FINANCIAL PERFORMANCE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2021-2023 - Biki, Fathrisya Nur Handayani; Sahmin Noholo; Mentari Rizki Sawitri Pilomonu (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) disclosure on financial performance, with institutional ownership as a moderation variable. This research was conducted on companies that are members of the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period using a quantitative approach. Sample selection was carried out by purposive sampling method, resulting in 39 samples of observation data for three consecutive years. The data analysis technique used is Structural Equation Modeling (SEM) which is operated through the WARP-PLS 7.0 program. The results of this study show that CSR has a positive but not significant effect on financial performance. Institutional ownership has a positive and significant effect on financial performance. Meanwhile, CSR moderated by institutional ownership has a positive and significant effect on financial performance.